The Differences in Effectiveness of Learning Using Contextual Teaching and Learning (CTL) and The Missouri Mathematics Project (MMP) in Terms of Mathematics Learning Outcomes - Yosepha P. W. Laja; Eduardus Beo Seso Delvion; Meiva Marthaulina Lestari Siahaan; Ermelinda Nainahas; Minanur Rohman (RANGE: Jurnal Pendidikan Matematika, 2024)
This study aims to compare the effectiveness of learning using Contextual Teaching and Learning (CTL) and the Missouri Mathematics Project (MMP) in terms of students' mathematics learning outcomes. The research method employed was an experiment with a pretest-posttest non-equivalent comparison-group design. The research population consisted of seventh-grade students, with the sample being students from class VII A using the CTL learning model and class VII B using the MMP learning model. The independent variable in this study is the learning model, while the dependent variable is the mathematics learning outcomes. The instruments used were a learning outcome test and an observation sheet for the implementation of learning. The results of the study indicate that both learning models, CTL and MMP, are effective in improving students' mathematics learning outcomes. The Wilcoxon test analysis showed that the significance values for both models were less than 0.05, indicating their effectiveness. However, the Mann-Whitney test revealed no significant difference in effectiveness between the two learning models. These findings suggest that both CTL and MMP can be used as effective alternative teaching methods to enhance students' mathematics learning outcomes. This study contributes to the selection of appropriate teaching methods to improve understanding and learning outcomes in mathematics. It is recommended for future researchers to investigate other aspects such as cognitive, psychomotor, or affective domains, and for teachers to consider using CTL and MMP in their teaching activities.